Relative reactivity of alkenyl alcohols in the palladium-catalyzed redox-relay Heck reaction - Hilton, Margaret J. (Tetrahedron, 2015)
The relative rates of alkenyl alcohols in the Pd-catalyzed redox-relay Heck reaction were measured in order to examine the effect of their steric and electronic properties on the rate-determining step. Competition experiments between an allylic alkenyl alcohol and two substrates with differing chain lengths revealed that the allylic alcohol reacts 3–4 times faster in either case. Competition between di- and trisubstituted alkenyl alcohols provided an interesting scenario, in which the disubstituted alkene was consumed first followed by reaction of the trisubstituted alkene. Consistent with this observation, the transition structures for the migratory insertion of the aryl group into the di- and trisubstituted alkenes were calculated with a lower barrier for the former. An internal competition between a substrate containing two alcohols with differing chain lengths demonstrated the catalyst’s preference for migrating towards the closest alcohol. Additionally, it was observed that increasing the electron density in the arene boronic acid promotes a faster reaction, which correlates with Hammett σ(p) values to give a ρ of −0.87.